Remediation of contaminated heavy metals and radionuclides of soil covering with the application of modern environmental technologies - Полевич, Олег Вадимович; Удалов, Ігор Валерійович; Кононенко, Аліна Володимирівна; Чомко, Федір Васильович (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
Formulation of the problem. The article is dedicated to the improvement of existing technologies for the restoration of soil contaminated with heavy metals (НM) by phytoremediation using artificially created geochemical barriers (GB). The purpose of the article includes 2 aspects: to develop and improve existing phytotechnology of soil purification through the use of GB; determine agrocenosis cultures for optimal phytoremediation of soil contamination by specific НM. Materials and methods. The ability of special agrocenoses to provide soil phytoremediation is used as the main working tool. Phytoremediation technology of contaminated VM soils involves two stages: preparatory and phytoremediation. In the first stage, geochemical survey of the territory of the landfill is carried out before the pollutants are introduced; an artificial GB is created from materials of industrial waste – iron sulfate (FeSO4 ∙ nH2O); the contaminated sites of the landfill are identified by sampling soil for analysis of the contents of НM. In the second stage of the experiment, the characteristics of the artificial artificial GB are determined and the process of soil phytoremediation using special agrocenoses is investigated. Quantitative determination of the content of НM in the selected samples is performed on a SRM-25 RF spectrometer. To analyze the content of HM, the plant material is dried to air-dry state, ground to a powdered state and pelleted under a press. Results. The analysis of the performed researches of phytoremediation technologies makes it possible to state with confidence that the most priority is the combination of phytoremediation technologies with the cessation of migration and concentration of НМ with artificial GB. As a result of the conducted research the following results are obtained: – existing phytotechnologies of soil purification are being improved due to the combination of artificially created GBs with selected agrocenoses; – it is established that the most representative pollutants of landfill soils are – Cu and Zn; – the optimal composition of agrocenoses for soil phytoremediation is determined: calendula, annual lupine and dwarf sunflower, which allow to obtain representative results on the efficiency of Cu and Zn phytochemical extraction. Maximum concentrations of Cu are recorded in sunflower tissues; high concentrations of Zn compared to Cu – in the tissues of calendula and lupine. The final part of the experiment is the elimination of agrocenosis at the final stage of vegetation, which accumulates in its composition high concentrations of Cu and Zn. It is estimated that in several cycles of elimination of such agrocenoses, the content of soil contaminants should reach acceptable levels. Scientific novelty and practical significance. Scientific novelty – the process of restoration of ecological properties of soils due to the improvement of phytoremediation technology is scientifically substantiated. The practical application of the obtained results is the implementation of the proposed technology of soil restoration in territories contaminated mainly by Cu and Zn.